2015
DOI: 10.1111/1755-5922.12113
|View full text |Cite
|
Sign up to set email alerts
|

miR‐30c Mediates Upregulation of Cdc42 and Pak1 in Diabetic Cardiomyopathy

Abstract: SUMMARYAim: Cardiac hypertrophy and myocardial fibrosis significantly contribute to the pathogenesis of diabetic cardiomyopathy (DCM). Altered expression of several genes and their regulation by microRNAs has been reported in hypertrophied failing hearts. This study aims to examine the role of Cdc42, Pak1, and miR-30c in the pathogenesis of cardiac hypertrophy in DCM. Methods: DCM was induced in Wistar rats by low-dose streptozotocin-high-fat diet for 12 weeks. Cardiac expression of Cdc42, Pak1 and miR-30c, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…Further investigation indicated that miR-30c possessed binding sites for the 3'-UTR and open reading frame (ORF) regions of Cdc42 and Pak1, and modulated Cdc42 and Pak1 expression levels in cardiomyocytes. In addition, miR-30c overexpression decreased HG-induced upregulation of Cdc42 and Pak1 and resulted in decreased expression levels of hypertrophic marker, atrial natriuretic peptide and a reduction in HG-treated cardiomyocyte cell size (35). These findings indicate that miR-30c exerts an anti-hypertrophic effect by inhibiting Cdc42 and Pak1 gene expression levels in DCM.…”
Section: Mir Involvement In the Pathogenesis Of Dcmmentioning
confidence: 73%
See 4 more Smart Citations
“…Further investigation indicated that miR-30c possessed binding sites for the 3'-UTR and open reading frame (ORF) regions of Cdc42 and Pak1, and modulated Cdc42 and Pak1 expression levels in cardiomyocytes. In addition, miR-30c overexpression decreased HG-induced upregulation of Cdc42 and Pak1 and resulted in decreased expression levels of hypertrophic marker, atrial natriuretic peptide and a reduction in HG-treated cardiomyocyte cell size (35). These findings indicate that miR-30c exerts an anti-hypertrophic effect by inhibiting Cdc42 and Pak1 gene expression levels in DCM.…”
Section: Mir Involvement In the Pathogenesis Of Dcmmentioning
confidence: 73%
“…1. Furthermore, numerous studies have demonstrated that interventions with the expression levels of associated miRNs may improve the pathophysiological process of DCM, providing novel insights into targets for the prevention and treatment of DCM (28,29,34,35,45). However, those studies were limited to the expression changes of miRs in heart tissue samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations